Reasons for attrition and retention among secondary school teachers in Niger State, Nigeria - Wushishi, Aminu Aliyu (2014)
Niger state is considered as one of the less educationally developed states in Nigeria with high attrition rate among secondary school teachers of about 47.5% between 2010-2012. This study explored reasons for attrition and retention among secondary school teachers in Niger state, Nigeria. A qualitative method was employed with the use of case study in order to have an in-depth understanding of the phenomenon under investigation. Twelve participants were selected. Nine serving teachers purposefully selected from three different secondary schools and three teachers who left the profession were reached through snowballing. All the participants were interviewed in English and each session of the interview lasted for about an hour to two hours. The interview was recorded, transcribed verbatim and analysed manually. In addition, observation took place in the schools and some documents related to the data were scrutinized. The trustworthiness of the study was ensured through triangulation, peer debriefing, member checking and Audit trail. The findings revealed that, language problem among students, delay in promotion,poor salary, late payment of salary, workload and large class size, poor status of teachers in the community and students’ disciplinary problems are among the major reasons for attrition among teachers. Another finding of the study discovered, increase in workload of the existing teachers, increase in the burden of school administration, affects students’ performance, cost implication in recruiting another set of teachers, as effects of teacher attrition. The findings also indicated that;housing and car loan, good working condition, regular promotion, regular payment of salary, increase in salary, spiritual motivation, support from school principals,opportunity for further studies and benefits from Endwell (Teachers’ Financial Cooperative Association) as reasons for retention among teachers in Niger state secondary schools. Based on the findings certain recommendations were proffered,these includes; Government should consider increasing the teachers’ salary above all other staff in the state, considering the importance of education and the role of teachers as prime movers. Government should make the payment of teachers’salaries as prompt as possible and their promotion should be regular as stipulated in the state civil service rules. On the issue of language problem among students,government should cancel the use of English as official languages and one major local should be adopted as official language as done in many South-East Asian countries. Government should provide a sort of car and housing loan to teachers so as to ease their transportation problems and enable them settle in their own houses. Principals should also support the novice teachers by giving them all the necessary support so as to enable them have confidence in the teaching profession.